Comparative analyses of angiosperm secretomes identify apoplastic pollen tube functions and novel secreted peptides - Flores-Tornero, María; Wang, Lele; Potěšil, David; Hafidh, Said; Vogler, Frank; Zdráhal, Zbyněk; Honys, David; Sprunck, Stefanie; Dresselhaus, Thomas (Plant reproduction, 2021)
Analyses of secretomes of in vitro grown pollen tubes from Amborella, maize and tobacco identified many components of processes associated with the cell wall, signaling and metabolism as well as novel small secreted peptides. Flowering plants (angiosperms) generate pollen grains that germinate on the stigma and produce tubes to transport their sperm cells cargo deep into the maternal reproductive tissues toward the ovules for a double fertilization process. During their journey, pollen tubes secrete many proteins (secreted proteome or secretome) required, for example, for communication with the maternal reproductive tissues, to build a solid own cell wall that withstands their high turgor pressure while softening simultaneously maternal cell wall tissue. The composition and species specificity or family specificity of the pollen tube secretome is poorly understood. Here, we provide a suitable method to obtain the pollen tube secretome from in vitro grown pollen tubes of the basal angiosperm Amborella trichopoda (Amborella) and the Poaceae model maize. The previously published secretome of tobacco pollen tubes was used as an example of eudicotyledonous plants in this comparative study. The secretome of the three species is each strongly different compared to the respective protein composition of pollen grains and tubes. In Amborella and maize, about 40% proteins are secreted by the conventional "classic" pathway and 30% by unconventional pathways. The latter pathway is expanded in tobacco. Proteins enriched in the secretome are especially involved in functions associated with the cell wall, cell surface, energy and lipid metabolism, proteolysis and redox processes. Expansins, pectin methylesterase inhibitors and RALFs are enriched in maize, while tobacco secretes many proteins involved, for example, in proteolysis and signaling. While the majority of proteins detected in the secretome occur also in pollen grains and pollen tubes, and correlate in the number of mapped peptides with relative gene expression levels, some novel secreted small proteins were identified. Moreover, the identification of secreted proteins containing pro-peptides indicates that these are processed in the apoplast. In conclusion, we provide a proteome resource from three distinct angiosperm clades that can be utilized among others to study the localization, abundance and processing of known secreted proteins and help to identify novel pollen tube secreted proteins for functional studies.
Keywords: Secretome; Pollen tube; kukuřice setá; Cell wall; Amborella; pylová láčka; Ovule; Signaling; vajíčko rostlin; Zea mays; Maize; Pollen Tube; Nicotiana; Magnoliopsida; Peptides; peptidy; Proteomics; Tobacco; CRP; tabák